Foot stiffening during the push-off phase of human walking is linked to active muscle contraction, and not the windlass mechanism. Issue 168 (15th July 2020) - Farris, Dominic James; Birch, Jonathon; Kelly, Luke
Abstract : The rigidity of the human foot is often described as a feature of our evolution for upright walking and is bolstered by a thick plantar aponeurosis that connects the heel to the toes. Previous descriptions of human foot function consider stretch of the plantar aponeurosis via toe extension (windlass mechanism) to stiffen the foot as it is levered against the ground for push-off during walking. In this study, we applied controlled loading to human feet in vivo, and studied foot function during the push-off phase of walking, with the aim of carefully testing how the foot is tensioned during contact with the ground. Both experimental paradigms revealed that plantar aponeurosis strain via the 'windlass mechanism' could not explain the tensioning and stiffening of the foot that is observed with increased foot-ground contact forces and push-off effort. Instead, electromyographic recordings suggested that active contractions of ankle plantar flexors provide the source of tension in the plantar aponeurosis. Furthermore, plantar intrinsic foot muscles were also contributing to the developed tension along the plantar aspect of the foot. We conclude that active muscular contraction, not the passive windlass mechanism, is the foot's primary source of rigidity for push-off against the ground during bipedal walking.